Gestational surrogacy in the Czech Republic - David Rumpik; Tatana Rumpikova; Michal Pohanka; Pavel Ventruba; Silvie Belaskova (Biomedical Papers, 2019)
Background: Gestational surrogacy, is a treatment option for women with certain clearly defined medical problems, usually an absent uterus, to help them have their own genetic children. The aim of our study was to review, evaluate and share our experience and outcomes over the last 13 years of the largest surrogacy program in the Czech republic. Methods: A total of 75 intended mothers and 82 surrogate mothers participated in this study. A retrospective cohort study was performed. Anonymized data were collected on 130 cycles of gestational surrogate (2004-2017) directly from the Clinic database. Results: We performed 130 in vitro fertilization cycles with gestational surrogacy which involved 73 fresh embryo transfers and 57 frozen embryo transfers. We achieved 57 (43.9%) pregnancies and 42 (32.3%) live births. The rate of multiple pregnancies was only 2.3 %. The most common indication for using was an absent or damaged uterus (65%), followed by medical conditions precluding pregnancy (23%) and repeated in vitro fertilization cycles or pregnancy failure (12%). Conclusion: In the 14 years of our experience, we have shown that treatment of young women with specific indications for gestational surrogacy is beneficial, successful and relatively free of complications. However, it is imperative to follow the medical indications for this treatment and specialist recommendations.